Evaluation and Standardisation of the Antioxidant Properties of Two Indian Remedies with Biochemical Test Assays - Janisch, Kerstin M.; Milde, Jens; Elstner, Erich F. (Arzneimittelforschung, 2005)
Two drugs composed of several different plant extracts are in use in Ayurvedic medicine for the treatment of asthma and arthritis, respectively. There is increasing evidence that reactive oxygen species (ROS) arising from several enzymatic reactions are mediators of inflammatory events such as the above mentioned. Plant extracts have the potential for scavenging such reactive oxygen species, dependent on the individual test system. Using biochemical model reactions relevant for the formation of ROS in vivo at inflammatory sites, inhibition of the indicator reaction for the formation of ROS is thought to represent a potential mechanism of the physiological activity of the corresponding preparation.
Keywords: AsmakureTM; Ayurveda remedies, antioxidant effects, biochemical model reactions, inflammation; PanekureTM; Reactive oxygen species